Plant invasions across the Northern Hemisphere: a deep‐time perspective. (6th May 2013) - Fridley, Jason D.
Abstract : Few invasion biologists consider the long‐term evolutionary context of an invading organism and its invaded ecosystem. Here, I consider patterns of plant invasions across Eastern North America, Europe, and East/Far East Asia, and explore whether biases in exchanges of plants from each region reflect major selection pressures present within each region since the late Miocene, during which temperate Northern Hemisphere floras diverged taxonomically and ecologically. Although there are many exceptions, the European flora appears enriched in species well adapted to frequent, intense disturbances such as cultivation and grazing; the North American composite (Asteraceae) flora appears particularly well adapted to nutrient‐rich meadows and forest openings; and the East Asian flora is enriched in shade‐tolerant trees, shrubs, and vines of high forest‐invasive potential. I argue that such directionality in invasions across different habitat types supports the notion that some species are preadapted to become invasive as a result of differences in historical selection pressures between regions.